If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(k + 8) + 3 = 2k + -7 Reorder the terms: 3(8 + k) + 3 = 2k + -7 (8 * 3 + k * 3) + 3 = 2k + -7 (24 + 3k) + 3 = 2k + -7 Reorder the terms: 24 + 3 + 3k = 2k + -7 Combine like terms: 24 + 3 = 27 27 + 3k = 2k + -7 Reorder the terms: 27 + 3k = -7 + 2k Solving 27 + 3k = -7 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. 27 + 3k + -2k = -7 + 2k + -2k Combine like terms: 3k + -2k = 1k 27 + 1k = -7 + 2k + -2k Combine like terms: 2k + -2k = 0 27 + 1k = -7 + 0 27 + 1k = -7 Add '-27' to each side of the equation. 27 + -27 + 1k = -7 + -27 Combine like terms: 27 + -27 = 0 0 + 1k = -7 + -27 1k = -7 + -27 Combine like terms: -7 + -27 = -34 1k = -34 Divide each side by '1'. k = -34 Simplifying k = -34
| 0.3*0.9= | | 5(x+2)+3=6(3x+9)-2 | | 5Xv-18-4=-36 | | 1/2k-3=-9x-4 | | 4/5=10/3x | | 3/4x-2/3=7/12 | | 3x^2-42x+135=0 | | 4/5=10/3 | | 1-9/5x3 | | -8g+10=-10-12g | | x+-4=-15 | | X=4(1)+8 | | p-25/140=12/42 | | 15/16x=11 | | 4x^2(x^2+6xy-7y^2)=x | | .6(x+8)-.8(5x+2)=10 | | 3/7/6 | | 2x+2(3x+4)=8+8x | | -4x^2+3=-6 | | 12=-r+11 | | (6x+7)-29=6x | | -3(2x+1)+x=2-(4x-2) | | 9x-10y=-13 | | 1/4(-8g+24)=g | | 5v-4-6=15+4v | | 4x+14=11x-2 | | 2x+63=9 | | ((1/t)-1)/(t-1) | | 7(4n+4)-10= | | -40n-43=3n | | 8n+8(n+7)=-35+3n | | ((x^8y^-4)/(16^(4/3)))^(-1/4) |